The Influence Of ISO 9001:2015 Quality Management System Implementation On Employee Performance With Organizational Commitment As A Mediating Variable At PT Intan Prima Kalorindo - Feby Kurnia; Raniasari Bimanti Esthi (Jurnal Ekuilnomi, 2025)
At PT Intan Prima Kalorindo, we hope to find out how the new ISO 9001:2015 Quality Management System affected employee performance through the medium of organizational commitment.  Researcher used SmartPLS 4.0 to examine the data and quantitative technique.  Organisational commitment which in turn has a major impact on staff performance, was found to be influenced by the implementation of ISO 9001:2015. Furthermore, organizational commitment mediates the relationship between the implementation of ISO 9001:2015 and employee performance which reinforces the importance of structured quality management in increasing employee engagement and productivity. These findings highlight the need for continuous improvement in quality management practices to cultivate a committed workforce and improve overall performance. The implications of this study emphasize the important role of quality management in driving employee performance and organizational success in the economic sector